Microcontroller-Based DHT11 Sensor for Temperature and Humidity Measurement - Muhammad Yunus (Akademi Teknologi Industri Dewantara Palopo, 2025)
Technological developments for temperature and humidity measurement systems have experienced significant progress through the use of microcontroller-based sensors. This research aims to measure temperature and humidity using a microcontroller-based sensor. The sensor used is a DHT11 connected to a NodeMCU ESP8266 microcontroller as a data processing centre. The data collection process was carried out from 09:00 to 17:00 every 2-hour interval. Data from temperature and humidity measurements were at 09:00, the temperature was 30°C with a humidity of 73%, then when the temperature increased at 11:00 (32°C) and reached its peak at 13:00 (33°C), the humidity actually decreased to 67% and 62%. Furthermore, when the temperature began to decrease at 15:00 (31°C) and 17:00 (29°C), the humidity increased again to 70% and 75%. The higher the air temperature, the relative humidity tends to decrease, and vice versa. Microcontroller-based DHT11 sensor is an effective solution in environmental monitoring systems that require practicality and efficiency.